Aggregation Model of Definitions of Rural Production of Zone Specializations and the Development of Rural Areas in RA - Manasyan, Volodya (Bulletin of Yerevan University G: Economics, 2014)
The article analyzes the social-ecological-economic problems of the development of rural areas of RA, the possibilities of overcoming them by precision of the priority zone specializations of intersectoral structure and market competitiveness growth of rural production. The author proposes the algorithm identifying priority specialization of Akhuryan region (Shirak region) considering its agro-climatic potential and economic features.
Keywords: rural areas, market competitiveness, zone specialization, algorithm, integral indicators, methods of decision, regional and community forms